MENINGKATKAN KEAKTIFAN BELAJAR BILANGAN BULAT SISWA KELAS V MELALUI MODEL PEMBELAJARAN BAMBOO DANCING - Dyah Tri Wahyuningtyas (Universitas Sarjanawiyata Tamansiswa, 2017)
Negative perceptions about math in elementary school students resulted in less active students in the learning process, student engagement in learning is very important for students to understand the material presented. Based on these problems, teachers need to develop innovative learning models that can melibatka Math students in the learning process. This study aimed to describe the learning that can improve the activity of learning integers fifth grade students through a learning model Bamboo Dancing. The research method is a classroom action research with research subjects fourth grade students of SDN 35 Kebonsari 1 Malang. The products of this research is learning design study model bamboo dancing. The results show the percentage of students 'learning activeness in the first cycle of 80% with good liveliness criteria, then the second cycle students' learning activeness on the second cycle increased to 92.5% with the liveliness of the criteria very well. Based on this model study of bamboo dancing can enhance the activity of learning integers fifth grade students of SDN Kebonsari 1 Malang.